Effect of Biochar on the Production of L-Histidine From Glucose Through Escherichia coli Metabolism - E, Yang; Meng, Jun; Cai, Heqing; Li, Caibin; Liu, Sainan; Sun, Luming; Liu, Yanxiang (Frontiers in Bioengineering and Biotechnology, 2021)
The organic compounds from biochar play a role of hormone analogs, stimulating the expression of metabolites by controlling related gene and protein. In this experiment, we reported the L-histidine biosysthesis was promoted by biochar treatment in E. coli unlike genetic engineering of the traditional method. The related results indicated the most optimal concentration was found to be 3%, and 7% is the lethal dose. E. coli was inhibited in the high-concentration treatment. On the other hand, docking technology was usually used as drug screening, basing on Lock-and-key model of protein in order to better understand mechanisms. So the organic compounds of biochar from GC-MS analysis that acted as ligands were connected to HisG protein controlling L-histidine biosysthesis in E. coli. The result showed that the three organic molecules interacted with HisG protein by hydrogen bond. So we considered that these three compounds play regulatory roles in L-histidine biosysthesis, and the hisG gene expression fully supports this conclusion.